Forensic entomology in Cameroon (Central African sub-region): the use of arthropod fauna of rat (Rattus norvegicus, Berkenhout, 1769, var. Wistar) carcasses as silent crime scene witnesses - Feugang Youmessi, Francis Dupont (Frontiers in Ecology and Evolution, 2025)
Globally, in order to solve a crime during a legal procedure, the presentation of palpable proof at court is the main tool. The contribution of necrophagous insects to this issue has recently increased as these invertebrates appear to comprise one of the major modern methods for the reinforcement of the judiciary system. This scientific discipline known as forensic entomology is a field of criminalistics/criminology that aims to use the results gathered from the study of insects collected at a crime scene in order to solve crimes involving wildlife or other animals/humans. In court, questions such as the estimation of the time of death, the cause of death, the movement of the corpse after death, and neglect of elderly are recurrent during a criminal investigation. In order to gather data that can be exploited to answer the aforementioned questions, we conducted, from March 18 to June 12, 2023, an experiment on carcasses of rats (Rattus norvegicus, Berkenhout, 1769, var. Wistar) within the University of Yaounde 1 campus. These were exposed to an open-air environment inside a wooden cage for protection in the bush behind Amphitheater 502 of the Faculty of Science of the University of Yaounde 1. The aim of this research work was to census necrophagous arthropod fauna that can always be exploited as harmless witnesses at the crime scene in order to determine the time of death, the cause of death, and the movement of the carcass after the crime. A total of 2,345 arthropod fauna belonging to three classes (Arachnida, Myriapoda, and Hexapoda), 16 orders (Acari, Araneida, Chilopoda, Diplopoda, Diptera, Coleoptera, Lepidoptera, Dermaptera, Hemiptera, Hymenoptera, Dictyoptera, Collembola, Homoptera, Orthoptera, Psocoptera, and Thysanura), 37 families, 14 genera, and 27 species were included in the census. This cadaveric fauna, referred to as “silent crime scene witnesses,” constitutes many trophic guilds such as predators, necrophagous and omnivorous, with 541, 1,289, and 294 insects, respectively. The aforementioned leading guilds were secondarily followed by saprophagous, opportunists, parasitoids, hematophagous, and accidental host, with 122, 85, 8, 3, and 2 individuals, respectively. The present preliminary forensic entomology research work obtained a high biodiversity of necrophagous arthropod fauna from the study site, which showed the presence of several trophic guilds that can potentially be used as accurate tools during faunal criminal inquiries within the Central African sub-region.